‘Contour bunding’ preserves soils and boosts farmers’ incomes by 20% in Mali – new study - CGIAR Research Program on Water, Land and Ecosystems (2017)
The participatory watershed management approach helped identify challenges land management. Changes in land use, water consumption for major crops were determined and the benefits of SWC practices evaluated through field experiments. Contour bunding can now be scaled through collective action of researchers, extension workers, NGOs and local community based organizations